1985
DOI: 10.1111/j.1600-0528.1985.tb00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental attendance and dental status

Abstract: This article examines the relationship between differences in dental attendance patterns and variations in dental status. A sample of 336 dentate men and 110 dentate women were selected at random from employees of two industrial plants in N.W. England in 1980. They were given a dental examination and asked about visits to the dentist. Regression analysis showed that while the more frequent the dental visits, the lower the rate of tooth loss and the fewer the number of teeth with active decay, the higher, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 0 publications
6
67
0
2
Order By: Relevance
“…In one study the intervention appeared free at the point of use to all participants, 48 in seven the intervention appeared free at the point of use to some members of the study population, 31,41,65,83,91,94,97 and in two the system of access was not clear but high coverage of the target population was reported. 88,90 In 19 studies insufficient information was provided to ascertain the study sample's access to the required intervention.…”
Section: Access To Intervention (Dental Check)mentioning
confidence: 99%
See 1 more Smart Citation
“…In one study the intervention appeared free at the point of use to all participants, 48 in seven the intervention appeared free at the point of use to some members of the study population, 31,41,65,83,91,94,97 and in two the system of access was not clear but high coverage of the target population was reported. 88,90 In 19 studies insufficient information was provided to ascertain the study sample's access to the required intervention.…”
Section: Access To Intervention (Dental Check)mentioning
confidence: 99%
“…37,41,48,88,90, 92-94,100(a),100(b),100(c) Fifteen studies relied on the reports of individuals' dental check frequency behaviour from self-administered questionnaires or interviews. 25,31,49,57,58,[60][61][62]64,65,71,83,85,91,97 In three it was not clear how dental check frequency was ascertained. 98(a),98(b), 98(c) Information about payment systems to dental practitioners was poorly reported.…”
Section: Interventions and Comparatorsmentioning
confidence: 99%
“…6 On the other hand, there is a large amount of evidence about the benefit of regular dental attendance -for example, less untreated decay, a lower rate of tooth loss and a higher number of functioning teeth (restored or otherwise sound teeth). 4,6 Furthermore, it has been argued that regular dental attenders experience less pain, have less 'gaps' from tooth loss and have less untreated disease. 2 There is currently a growing interest in oral health outcomes in terms of how oral health affects quality of life.…”
mentioning
confidence: 99%
“…5,6 It has also been suggested that regular dental attendance may not help prevent the onset of further dental disease. 6 On the other hand, there is a large amount of evidence about the benefit of regular dental attendance -for example, less untreated decay, a lower rate of tooth loss and a higher number of functioning teeth (restored or otherwise sound teeth). 4,6 Furthermore, it has been argued that regular dental attenders experience less pain, have less 'gaps' from tooth loss and have less untreated disease.…”
mentioning
confidence: 99%
“…There is an urgent need for evidence-based papers like this, as we increasingly face patients armed with extensive 'reading off the Internet' -some of which is simply wrong, but a lot is opinion -which we have difficulty finding research for or against, because we are so busy simply doing the work! A lot of the statements made in this paper simply either reinforce or contradict current professional dogma, without providing us with the tools for making our own minds up on the validity ( [1][2][3] The average number of restorations placed also increased significantly with a change in dentist. 2 The lowest survival of restorations was strongly and directly related to the shortest median frequency of attendances, due possibly to the higher occurrence of dental problems in the most frequent attendees.…”
Section: G E Cooper C J Tredwin N T Cooper a Petrie And D mentioning
confidence: 77%